Total Suspended Solids in Teluk Awur, Jepara using Red Reflectance from Landsat-8 - Andhita, Laviola Reycha Fitri; Maslukah, Lilik; Wirasatriya, Anindya; Indrayanti, Elis; Prasetyawan, Indra Budi (Jurnal Kelautan Tropis, 2024)
The coastal waters of Teluk Awur, Jepara are affected by human activities such as aquaculture, tourism, agriculture, and settlements. The number of human activities on land will contribute to high suspended solids (TSS) entering coastal waters by run-off. The high TSS in coastal areas will affect the entry of light intensity, disrupting the photosynthesis process and ecosystem. This study compares TSS values based on Landsat images using several TSS algorithms such as Wirasatriya, Budhiman, Ajiperwata, and Parwati algorithms and the algorithm resulting from the July 2023 field data calibration against red reflectance. The algorithm's performance from calibration has a smaller error value with RMSE = 8.51, MAPE = 25.77%, and Bias = 7.52. TSS estimation from Landsat 8 satellite imagery has a range of values of 30.56 - 62.55 mg/L (average 35.60 mg/L), while field measurements of TSS values are 22.40 - 64.52 mg/L (average 32.69 mg/L). This research will be valuable information for using the right Landsat-8 algorithm for temporal and sustainable TSS monitoring. It can be used in abrasion monitoring and management in the Teluk Awur coastal waters of Jepara.